Gene assembly via one-pot chemical ligation of DNA promoted by DNA nanostructures. Issue 36 (17th April 2018) - Manuguerra, Ilenia; Croce, Stefano; El-Sagheer, Afaf H.; Krissanaprasit, Abhichart; Brown, Tom; Gothelf, Kurt V.; Manetto, Antonio
Abstract : A gene was obtained from 14 oligonucleotides self-assembled and chemically ligated in a DNA nanostructure. Abstract : Current gene synthesis methods are driven by enzymatic reactions. Here we report the one-pot synthesis of a chemically-ligated gene from 14 oligonucleotides. The chemical ligation benefits from the highly efficient click chemistry approach templated by DNA nanostructures, and produces modified DNA that is compatible with polymerase enzymes.